The determinants of teachers’ satisfaction and its influence in strategic management of human resources in the institute of education sciences in Kwanza South province - Lunga, Domingos (2020)
The organizational environment is characterised by forces which affect the dynamics and the organizational competitiveness. These factors influence the strategy of the organization and its objectives. In this context, professional satisfaction adopts a growing interest in understanding quality of professional life, strategic management and organizational performance. Greater job satisfaction contributes to the professional finding meaning in his professional activity and adopting positive attitudes towards organizational performance. In this perspective, the article purposes to verify if there are differences between sociodemographic, professional, training and labour variables related to the level of satisfaction of the teachers that belong to the Institute of Education Sciences, as well as to know the level of satisfaction of these professionals. The results show that the level of teachers’ satisfaction is positive and allows to understand the determinants of teachers’ satisfaction and their mastery in strategic management of human resources and organizational competitiveness.